PENGARUH PENERAPAN SISTEM INFORMASI MANAJEMEN TERHADAP EFEKTIVITAS KERJA PEGAWAI DI INSTALASI RAWAT JALAN - A.Awaliya Anwar; Andi Khairul Musyawir; Era Pratiwi (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2020)
The purpose of this study was to analyze the effect of management information systems on the work effectiveness of outpatients at the Prof.Dr.H.M Anwar Makkatutu Regional General Hospital, Bantaeng Regency. The type of research used is quantitative research. This research method uses primary data through a survey using a questionnaire as many as 73 outpatient employees of the Regional General Hospital Prof.Dr.H.M Anwar Makkatutu Bantaeng as the research sample. Data were analyzed through univariate and bivariate analysis with Chi-Square test using SPSS program. The results showed that: (1) The quality of the system showed a value of p = 0.001 < from = 0.05, which means it can be concluded that Ho is rejected, meaning that the system user has an effect on the work effectiveness of outpatients at Prof. Hospital. Dr. H. M. Anwar Makkatutu 2020, (2) The quality of information affects the work effectiveness of employees with a p value = 0.000, (3) System users affect the work effectiveness of outpatients with a p value = 0.000, (4) User satisfaction affects the work effectiveness of outpatients path with p value = 0.000. This shows that the quality of the management information system can increase the work effectiveness of outpatient employees at Prof. Hospital. Dr. H. M. Anwar Makkatutu Bantaeng. If the management information system is good, it will increase the work effectiveness of outpatients and increase employee satisfaction.